Cation-dependent mannose-6-phosphate receptor expression and distribution are influenced by estradiol in MCF-7 breast cancer cells - Bannoud, Nadia (2018)
Cancer cells secrete procathepsin D, and its secretion is enhanced by estradiol. Although alterations in the pro-enzyme intracellular transport have been reported, the mechanism by which it is secreted remains poorly understood. In this work, we have studied the influence of estradiol on the expression and distribution of the cation-dependent mannose-6-phosphate receptor (CD-MPR), which would be a key molecule to ensure the proper localization of the enzyme to lysosomes in breast cancer cells. Immunoblotting studies demonstrated that the expression of CD-MPR is higher in MCF-7 cells, as compared to other breast cancer and non-tumorigenic cells. This expression correlated with high levels of cathepsin D (CatD) in these cells. By immunofluorescence, this receptor mostly co-localized with a Golgi marker in all cell types, exhibiting an additional peripheral labelling in MCF-7 cells. In addition, CD-MPR showed great differences regarding to cation-independent mannose-6-phosphate receptor. On the other hand, the treatment with estradiol induced an increase in CD-MPR and CatD expression and a re-distribution of both proteins towards the cell periphery. These effects were blocked by the anti-estrogen tamoxifen. Moreover, a re-distribution of CD-MPR to plasma membrane-enriched fractions, analyzed by gradient centrifugation, was observed after estradiol treatment. We conclude that, in hormone-responsive breast cancer cells, CD-MPR and CatD are distributed together, and that their expression and distribution are influenced by estradiol. These findings strongly support the involvement of the CD-MPR in the pro-enzyme transport in MCF-7 cells, suggesting the participation of this receptor in the procathepsin D secretion previously reported in breast cancer cells.